Noxious Stimuli Evoke a Biphasic Flexor Reflex Composed of A δ-Fiber-Mediated Short-Latency and C-Fiber-Mediated Long-Latency Withdrawal Movements in Mice - Satoko Kimura; Motoko Honda; Mitsuo Tanabe; Hideki Ono (Elsevier, 2004)
The nociceptive flexor reflex was studied in mice, focusing in particular on movement. Electrical stimuli delivered to the ventral aspect of the toe through a pair of needle electrodes inserted subcutaneously elicited a biphasic withdrawal reflex that was composed of short- and long-latency movements of the ipsilateral hind paw. The first response had a lower activation threshold compared with the second movement. Similar biphasic responses were observed in the afferent volley recorded from the sciatic nerve as well as in the electromyographic activity recorded from the femoris biceps muscle. Tetrodotoxin, applied over the sciatic nerve, abolished the first movement, but the second response was preserved, revealing that the first movement was elicited by the activation of myelinated Aδ-fibers, whereas the second movement was mediated by unmyelinated C-fibers. Thus, simultaneous activation of Aδ- and C-fibers leads to separate, but sequentially occurring withdrawal movements of the hind paw in mice. Systemic administration of morphine suppressed the withdrawal reflex, which was attributable to a preferential reduction of the Aδ-fiber-mediated short-latency component. This method will be useful for understanding how Aδ-fiber- and C-fiber-mediated nociceptive reflexes are affected by drugs in the whole animal system. Keywords:: flexor reflex, myelinated Aδ-fiber, unmyelinated C-fiber, tetrodotoxin, morphine